Infective endocarditis in patients with artificial heart valve – an unappreciated and threatening problem - Trzeciak, Przemysław; Poloński, Lech; Zembala, Marian (Przewodnik Lekarza/Guide for GPs, 2007)
Every patient with artificial heart valve prosthesis is in a group of high risk of infective endocarditis (IE). The case report of a 52-year-old woman after artificial mitral valve replacement is presented. Two months later the patient was reoperated on due to IE and prosthesis dysfunction in the course of urosepsis. In the paper the diagnostic and therapeutic procedures for which prophylaxis against infective endocarditis is recommended have been identified. The standard therapy for prophylaxis against IE is presented. The other cardiac conditions predisposing to endocarditis demanding antibiotic prophylaxis before dental procedures have been mentioned. Cooperation of the cardiac surgeon, cardiologist, general practitioners and other specialists allows the risk of IE to be reduced.